PENGARUH FREKUENSI PERDAGANGAN , TRADING VOLUME, NILAI KAPITALISASI PASAR, HARGA SAHAM, DAN TRADING DAY TERHADAP RETURN SAHAM PADA PERUSAHAAN KOSMETIK DAN KEPERLUAN RUMAH TANGGA DI BURSA EFEK INDONESIA - Yusra, Muhammad (Department of Accounting, Faculty of Economics & Business, 2019)
The purpose of this study was to analiyze the effect of frequency of stock trading,trading volume,market capitalization value,stock price,and trading day on stock return of food and baverage companies listed on the IDX. The data used in this study were secondary data in the from of 2015-2018 financial statement obtained from 12 companies with 48 observations (balance panel data). The data were accessed on www.idx.co.id. The method of data analyze with the help of SPSS 16. The result of study found that the frequency of stock trading did not have a significant effect on stock returns, trading volume did not have a significant effect on stock returns, market capitalization value did not have a significant effect on stock returns, the stock price did not have a significant effect on stock returns, trading day did not have a significant effect on stock return.